Humanist interest or Protestant faith? Ferenc Bornemisza of Pest and his book collection (Case study) - Károlyi, Bálint (Egyháztörténeti Szemle, 2024)
A lot of research has been done on the Habsburg Monarchy. We have gained insights into politics, economics and social history. More recently there has also been work on the administrative segment, but this field has not been studied from a religious and cultural history perspective. The study of the culture and literacy of the officials of the Habsburg Monarchy is a relatively new field of research. A more thorough analysis of individual book lists or libraries provides important information on the level of knowledge and education of individual officials and the group as a whole. Ferenc Bornemisza was one of the several officials of the Hungarian Chamber in the 16th century. A paper about his life was published earlier. But his knowledge and cultural background are as little known as those of his contemporaries. His list of books gives us an interesting insight into the contact between the Reformation and humanism among the office holders. As a clerk in the Hungarian Chamber, he was a devout Catholic, but his small collection of books shows that he was interested in the Reformation. He also had several clerical works and some high-quality humanist books. Luther, Melanchthon, Sylvester and Pesti are some of the authors in his collection. The religious works of these Lutheran reformers and humanist scholars of the period testify to the complex interest of a financial official. In my presentation, I will demonstrate Bornemisza’s personal contact to the Reformation. My main question is: was he a Protestant official? Was he a humanist with interest on the new spiritual and intellectual trends? Or his life and his booklist is telling us something different? Was he alone among his fellow officials in the chamber or were there others like him?